Gender Political Discourse in Mauritania from 2009 to 2018 : A Dissertation submitted in Partial Fulfillment of the Requirement for the Doctoral Degree - Khouya Mariem (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et des Sciences Humaines - Saïs- , Fès, 2019)
This dissertation project explores three main important issues, gender, discourse and politics in relation to the Mauritanian context. Though Mauritania has recently adopted strategies, through positive discrimination, to engage women into politics, women are still under-represented. In this respect, the aim of the thesis is to understand the dimensions and circumstances surrounding Mauritanian women’s inclusion into politics and to deconstruct the feminine ‘domestic’ subject analyzing the Mauritanian sociocultural perceptions of the effective political actor. Admitting that power relations shape women’s position in language and that since there is no existence beyond discourse, the study aims at analyzing women’s political discourse as well as the representation of femininity both in the discourse female political actors and their male counterparts’. Two types of data are conducted for the study. The data that are meant for the investigation of Mauritanian women’s political participation is released through the questionnaire and the interview. Concerning the second type of data that is conducted for the evaluation of women’s political participation it is based on applying different approaches to Critical Discourse Analysis on 50 political discourses that are delivered by Mauritanian women politicians in different political events. The study achieved a number of results the most important of which are: Mauritanian women’s political participation is influenced by traditional gender roles. Women are associated with positions that are attached to the private sphere. More significantly, another important point which the study reaches is that the majority of Mauritanian women politicians are satisfied with the inferior political role they play. Moreover, it has been observed that Mauritanian women politicians use the discursive style that is labeled as masculine. This is that women politicians II depersonalize some aspects of their feminine identity and categorize themselves more with the image of the masculine leader. The results of the study reflect that the majority of Mauritanian women political actors do not have feminist orientation. The absence of feminist orientation is noticed in different aspects of Mauritanian women’s political discourse, which contributes to their political passivity.
Keywords: Littérature et Communication; Political discourse; Feminine political discourse; Masculine political discourse; Women’s political participation; Feminine identity construction